UPAYA MENINGKATKAN KETERAMPILAN MENULIS TEKS EKSPLANASI DAN HASIL BELAJAR BAHASA INDONESIA DENGAN METODE INKUIRI PADA SISWA KELAS XI IPS 1 SMA NEGERI 3 METRO - Cik Ayu Kesuma (Ksatra: Jurnal Kajian Bahasa dan Sastra, 2020)
This study aims to describe the improvement of skills and learning outcomes of Indonesian language, especially writing explanatory text for class XI IPS 1 SMA Negeri 3 Metro using the inquiry method. The research design used was classroom action research. Methods and data collection tools using test and non-test techniques (observation, documentation, and interviews). The results showed an increase in explanatory text writing skills in the pre-cycle an average of 79.25%, in the first cycle it became 96.83, in the second cycle the explanatory text writing skill was 108.91, and the third cycle was 200.16. The increase in pre-cycle 17.25%, cycle II to 12.08% and to cycle III to 91.25%. Furthermore, the average pre-cycle Indonesian learning outcomes were 5, cycle I got an average of 7, cycle II became 8, and cycle III became 9. The increase in pre-cycle to cycle I was 2%, cycle I to cycle II was 1%, cycle II to cycle III to 1%.